Clinical utility of an assessment scale for engagement in activities for patients with moderate‐to‐severe dementia: additional analysis. Issue 4 (17th April 2022) - Tanaka, Hiroyuki; Umeda, Ren; Kurogi, Tatsunari; Nagata, Yuma; Ishimaru, Daiki; Fukuhara, Keita; Nakai, Shunsuke; Tenjin, Masahiro; Nishikawa, Takashi
Abstract: Background: We developed the assessment scale for engagement in activities (ASEA), an assessment tool used to quantify engagement in therapeutic activities for patients with moderate‐to‐severe dementia. In this study, we report additional analyses to confirm the viability of ASEA as a reliable measurement scale. Methods: This study included 195 patients with moderate‐to‐severe dementia in a psychiatric acute‐phase hospital. Additional analyses based on the Consensus‐based Standards for the Selection of Health Measurement Instruments (COSMIN) checklist were as follows: (i) exploratory and confirmatory factor analysis; (ii) standard error of measurement (SEM), minimal detectable change (MDC) and limit of agreement (LOA); (iii) short change score from baseline to 2 weeks; and (iv) correlation to the facial expression analysis system. Results: Exploratory factor analysis yielded two factors. This two‐factor model of ASEA exhibited an acceptable and validated model fit (comparative fit index = 0.954, Tucker Lewis index = 0.936, goodness‐of‐fit index = 0.927, adjusted goodness‐of‐fit index = 0.873, root mean square error of approximation = 0.091, standardised root mean square residual = 0.045) by confirmatory factor analysis. SEM and MDC were 1.29 and 3.80, respectively. The Bland–Altman plot for examining LOA showed no apparent fixed bias. From baseline to 2 weeks later, 129 participants were retested. The mean ASEA total score improved significantly (Wilcoxon signed‐rank test; P  < 0.01, effect size = 0.25) from baseline (14.30 ± 2.63) to 2 weeks later (15.00 ± 2.73). The correlation between each emotion value was calculated using Kokoro sensor, which is an affect analysis based on human facial expression data using deep learning. For the 36 video data samples, the total score and domains of arousal, interaction, and affect in ASEA were statistically significantly correlated with the emotion value of joy, engagement, and valence (Spearman rank correlation; P  < 0.05). Conclusions: Among the few evaluation methods specific to severe dementia, ASEA is a useful scale for quantifying and evaluating the state of engagement in therapeutic activities.